Integrated energy system multi-level planning model based on scenario reasoning, equipment selection, and capacity optimization. Issue 14 (14th November 2022) - Wang, Yongli; Zhang, Danyang; Zhou, Minhan; Song, Fuhao; Liu, Lin; Liu, Yang; Zhu, Jinrong
ABSTRACT: The Integrated Energy System fulfilled coordinated planning, optimized operation, coordinated management, which can improve energy efficiency and reduce energy costs. A multi-level planning optimization model with integrated energy system scenario reasoning, equipment selection, and capacity optimization is proposed. The minimum life cycle cost of integrated energy system is taken as the objective function, and the constraints of scenario reasoning, equipment selection and capacity optimization are also taken into account, including the similarity between planning scenarios and historical scenarios, equipment model matching and mutual exclusion, and operational constraints. In addition, an improved particle colony-ant colony optimization algorithm is used to solve the model. The K-proximity reasoning method is constructed based on multiple data types for reasoning of the equipment scenario in the park. The optimized results are transferred to the case library to further enrich the planning scenario case library. Finally, a park is taken as an example to analyze the impact of equipment-type changes on the planning results and provides important suggestions for the park construction.